Application development for Software-Defined networks in state of the art controllers - Correia, Jorge Filipe Henriques (2016)
In the last few years, the importance of the internet in our lives increased considerably. Networks have become a big part of our lives and there will be a setup almost everywhere we go: in our homes, in the workplace, in stores, in universities, in the subway. Each and every one of these places has a network, a router, Wi-Fi, etc. Due to its high importance, service providers must guarantee a fully operational network, 24 hours a day, leaving no room for mistakes. However, that creates a problem: how can developers test new protocols? In no way is a service provider willing to risk ruining its network because a developer tested a non-working protocol. Researchers who dedicate themselves to the study of these frameworks believe that the main problems of a fully operational network lie essentially in its architecture, as network devices incorporate different and quite complex functions. Major networks, such as service providers, are built upon robust architectures with the ability to support large traffic volumes, with different characteristics. The service provider is able to process large amounts of data simultaneously, as well as route and forward traffic. As they have built-in control functions that work in a distributed manner and considering they are made by a limited number of manufacturers, these networks present several limitations. Besides its complexity and configuration, it must be taken into account that every network should be prepared to deal with potential failures that might occur, as well as any security-related problems. A network - regardless of its level of use - must allow its users to use it as safely as possible. Networks today have poor flexibility and their development, growth and innovation are far from simple. Thus, the provision of more diversified services to satisfy the users presents a challenge to service providers, since the system and the administration functions are separated. The answer to these problems lies within the Software-Defined Networks (SDN), given that they seem to be very promising as far as innovation is concerned, allowing the development of new strategies and management control networks. These networks use programmable switches and routers that can process packets of data for several isolated experimental networks simultaneously, through virtualization. These networks run in the Control Plane, in servers operating separately from the network devices. This gives the network administrator a greater control over the network, as it allows to manage different resources by directing them to different traffic flows. A SDN using OpenFlow is capable of supporting a high-response network to each and every controller failures that might occur, without slowing the network's response, as it offers great flexibility and helps with fighting the limitations of any existing network. The main goal of this thesis is to explain how to use this new approach (SDN) and its capacities. This work will serve as a basis to all who wish to obtain new knowledge about this topic. One of the main focuses of this thesis is to pinpoint the advantages and disadvantages of SDN with an OpenFlow architecture.